Equações diofantinas lineares com n variáveis e aplicação em sala de aula utilizando o GeoGebra - Silva, Adna Leile Araujo Damasceno (2019)
The work described here is a proposal of inserting the content of linear diophantine equations for 9th grade students and a study of linear diophantine equations for three variables and also the general case with n variables variables. My objective was to analyze the process of transforming the content of linear diophantine equations for teaching purposes in basic education from topics of the theory of number theory. Such as divisibility, maximum common divisor, prime numbers and factorization, applying everyday problems involving linear diophantine equations. Geogebra software was used to analyze the results obtained from a proposed problem. By being presented to the content, students were able to identify actions that are practiced by them in everyday life that reflect a diophantine equation and could also verify that the solutions of diophantine equations correspond to points in the graph of a related function.